Towards a framework for adaptive web applications - Sampaio, Ana I. (2014)
We have developed a framework to support adaptive elements in Web pages. In particular we focus on adaptive menus. Developers are able to define rules for menu adaptation according to the features of the device and browser in use. This paper briefly describes the selected adaptation patterns and their implementation.